The Influence of Values and Achievement Motivation on Teacher Professionalism at Muhammadiyah 2 High School Yogyakarta, Indonesia - Suyatno; Wantini; Baidi; Amurdawati, Ganis (Pedagogika, 2019)
Teacher professionalism is one of the important aspects of improving the academic success of students. In order to establish teacher professionalism development programs, then it needs to be identified the factors which influenced it. The research that has been around so far tend to prioritize external factors than internal factors, whereas according to a literature review, the researcher finds that internal factors have more impact on the improvement of teacher professionalism. This study aimed to determine the influence of values and achievement motivation on teacher professionalism. This study used a quantitative research by testing hypotheses. The data sources were selected through saturated sampling techniques. The sample for this study consisted of 60 teachers from Muhammadiyah 2 High School Yogyakarta, Indonesia. The data was collected using a questionnaire. The collected data were analysed using simple regression and multiple regression techniques with the aid of SPSS statistics application. The results showed that the teacher‘s values had a positive and significant effect on the teachers’ professionalism with a correlation value of 0.562, achievement motivation had a positive effect on the professionalism of the teacher with a correlation value of 0.196, and values and achievement motivation had a simultaneous positive effect on the teachers’ professionalism with a correlation value of 0.616. These findings show that values and achievement motivation are important internal factors in an effort to improve the professionalism of teachers. The results of this study indicate that values could stand alone in improving teacher professionalism, while the achievement motivation has a positive and significant influence if it is simultaneously incorporated with values. These two internal aspects should be taken into consideration when formulating policies and programs for the improvement of teacher professionalism. Subsequent studies need to be held to identify factors that influence values and achievement motivation.